A NEW LOCATION SELECTION MODEL OF BUY ONLINE AND PICK UP IN STORE IN OMNICHANNEL LOGISTICS SYSTEMS - Min, Choon Ki; Cha, Eun Ju; Chang, Byeong Yun (International Journal of Industrial Engineering : Theory Applications and Practice, 2023)
The placement of buy online and pick up in store (BOPS) facilities is an essential consideration to ensure the efficient operations of omnichannel logistics systems. There have been many efforts to improve customer service and the cost of BOPS. This study suggests a structured model to propose an optimal location of BOPS. Firstly, we categorize and characterize the BOPS facilities type. Secondly, we offer evaluation criteria of the BOPS facilities with the fuzzy analytic hierarchy process (Fuzzy-AHP). Thirdly, we define each sub-criteria by equation and then calculate the fitness rankings of locations in a case study using public placement analysis data in South Korea. These results confirmed that the proposed method is a great guideline for real problems with the placement of BOPS facilities. This study proposes a methodology to solve location selection problems of BOPS with available public data, which can be practically applied to omnichannel logistics.
Keywords: Buy online and pick up in store; Customer-service; Essential considerations; Evaluation criteria; Fuzzy AHP; Location selection models; Logistics system; Offer evaluation; Optimal locations; Structured modeling; Buy Online and Pick Up in Store; Electronic Commerce; Fuzzy AHP; Logistics